Decentralisation of district health services in the Free State Province - Motsoari, Motsamai Clement (University of the Free State)
Experiments with decentralisation began in the late 1970s and continued throughout the 1980s. Decentralisation is regarded as a key element of the primary health care approach. It is initially seen as having important political value that can be used as a means to enhance health service policy. However, in many instances, western donors who believe that because one form of decentralisation works in developed countries, it will also work in the developing world often pursue decentralisation. The challenge facing the South African National Health System and the Free State Health System in particular, is to design a comprehensive programme to redress social and economic injustices brought about by apartheid to the majority of the population to ensure that emphasis is placed on health and not just medical care so that issues relating to socio-economic conditions such as poverty, water and sanitation, and proper housing should be addressed adequately. At present, implementation of the District Health System (DHS) based on primary health care (PHC) approach is provided by the Free State Department of Health (FSDOH) and by local municipalities on an agency basis. The above approach is concerned with keeping people healthy, as it is with caring for them when they become unwell. In an endeavour to address aforementioned challenges, the South African Government of National Unity (GNU) has adopted decentralisation as a model for both governance and management. Decentralised governance is embodied in the Constitution of the Republic of South Africa, 1996, in the form of powers and functions for the three spheres of government. The powers and functions of the local sphere of government bear testimony to the importance of this sphere in particular. The GNU, through its adoption of the Reconstruction and Development Programme (RDP) in 1994, committed itself to the development of a DRS based on PRC approach as enunciated at the Alma Ata conference in 1978. The hypothesis for this study indicated that decentralisation of DRS in the Free State Province will enhance efficiency and equity and thus make local public representatives accountable for services rendered. The hypothesis and research objectives for the study were validated by means of literature review and empirical survey. The thesis outlines the conceptualisation and forms of decentralisation and also draws lessons from the experiences of various countries including Canada, Zambia, Indonesia, and Brazil and highlights the need to approach the formulation and implementation strategies for health sector reforms systematically, rather than importing, uncritically, structural models developed abroad. Political considerations are inherent in any decision made and a political environment limits the extent of decentralisation. Without doubt, the most serious mistake any reformer can make is to assume decentralisation to be a managerial exercise devoid of political cause and consequences. The thesis concludes by presenting analysis and interpretation of research findings while also outlining key recommendations that might be of assistance for identifying an appropriate form for decentralisation of health services.
Thesis (Ph.D. (Public Management))--University of the Free State, 2012
Keywords: Primary health care -- South Africa -- Free State; Medical care -- South Africa -- Free State; Health planning -- South Africa -- Free State; Decentralization in government -- South Africa -- Free State; Public health administration -- South Africa -- Free State